Electrical impedance tomography as a bedside assessment tool for COPD treatment during hospitalization - Yang, Lin; Gao, Zhijun; Cao, Xinsheng; Sun, Shuying; Wang, Chunchen; Wang, Hang; Dai, Jing; Liu, Yang; Qin, Yilong; Dai, Meng; Guo, Wei; Zhang, Binghua; et al. (Frontiers in Physiology, 2024)
For patients with chronic obstructive pulmonary disease (COPD), the assessment of the treatment efficacy during hospitalization is of importance to the optimization of clinical treatments. Conventional spirometry might not be sensitive enough to capture the regional lung function development. The study aimed to evaluate the feasibility of using electrical impedance tomography (EIT) as an objective bedside evaluation tool for treatment of acute exacerbation of COPD (AECOPD).Consecutive patients required hospitalization due to AECOPD were included prospectively.EIT measurements were conducted at the admission and before the discharge simultaneously when forced vital capacity maneuver was conducted. EIT-based heterogeneity measures of regional lung function were calculated based on the impedance changes over time. Surveys for attending doctors and patients were designed to evaluate the ease of use, feasibility and overall satisfactory level to understand the acceptability of EIT measurements. Patient-reported outcome assessments were conducted. User's acceptance of EIT technology was investigated with a 5-dimension survey.A total of 32 patients were included and 8 patients were excluded due to FVC maneuver not meeting ATS criteria. Spirometry-based lung function was improved during hospitalization but not significantly different. (FEV1 %pred.: 35.8±6.7% vs. 45.3±8.8% at admission vs. discharge; p=0.11. FVC %pred.: 67.8±0.4% vs. 82.6±5.0%; p=0.15. FEV1/FVC: 0.41±0.09 vs. 0.42±0.07, p=0.71). The symptoms of COPD were significantly improved. but the correlations between improvement of symptoms and spirometry FEV1 and FEV1/FVC were low (R=0.1 and -0.01, respectively). The differences in blood gasses and blood tests were not statistically insignificant.All but one EIT-based regional lung function parameters were significantly improved after hospitalization. The results were highly correlated with patient-reported outcome assessment (R>0.6, P<0.001). The overall acceptability score of EIT measurement for both attending physicians and patients was high (4.1±0.8 for physicians, 4.5±0.5 for patients out of 5).These results demonstrated that it was feasible and acceptable to use EIT as an objective bedside evaluation tool for COPD treatment efficacy.